(untitled) (Applied Biological Research, 2013)
The present investigation was carried out at Research Farm, Division of FMAP, SKUAST-Kashmir, Shalimar, Srinagar, J&K (India) during the year2010 to evaluate the effect of two growth regulators viz., indole butyric acid (IBA) and naphthalene acetic acid (NAA) applied @ 500, 1000 and 1500 ppm on rooting of four commercial cut flower cultivars of rose viz., ‘Grand Gala’, ‘First Red’, ‘Naranga’ and ‘Noblesse’. Rooting characteristics were significantly improved by auxin treatments. Minimum days to root appearance(22.55) and maximum rooting (76.67%), primary root number (12.57), root length (5.87 cm) and field survival (73.13%) was recorded in cuttings treated with IBA @ 1500 ppm. Rooting parameters exhibited improvement with IBA in comparison to NAA application. Among the genotypes, ‘First Red’ proved superior to others exhibiting maximum rooting (66.67%), primary root number (11.29), root length (4.98 cm) and field survival (76.28%). Minimum days to root appearance (21.61) and maximum percentage of cuttings (13.81) with new leaf growth was observed in cv. ‘Noblesse’. Interaction effect between genotype and growth regulators was significant for most of the parameters studied.